Avascular necrosis: a growing concern for the HIV population. (6th June 2018) - Green, Kevin R; Hernandez-Jimenez, Jarelys M; Isache, Carmen Liliana; Jacob, Rafik
Abstract : A 33-year-old woman with history of HIV presented with 4 months of gradually progressing right hip pain and was found to have avascular necrosis (AVN) of both femoral heads. She had no other risk factors for AVN including sickle cell disease, systemic lupus erythematosus, prolonged steroid used or trauma. She initially failed conservative management and ultimately had bilateral hip core decompressions. After decompression therapy, the left femoral head collapsed and patient underwent a left total hip arthroplasty. Her postsurgical course was complicated by the left sciatic nerve neuropathy for which she is currently being managed with duloxetine. She has yet to follow-up with her orthopaedic surgeon for further evaluation.